2011
DOI: 10.1186/1743-422x-8-22
|View full text |Cite
|
Sign up to set email alerts
|

Oncolysis of malignant human melanoma tumors by Coxsackieviruses A13, A15 and A18

Abstract: Many RNA viruses are displaying great promise in the field of oncolytic virotherapy. Previously, we reported that the picornavirus Coxsackievirus A21 (CVA21) possessed potent oncolytic activity against cultured malignant melanoma cells and melanoma xenografts in mice. In the present study, we demonstrate that three additional Group A Coxsackieviruses; Coxsackievirus A13 (CVA13), Coxsackievirus A15 (CVA15) and Coxsackievirus A18 (CVA18), also have similar oncolytic activity against malignant melanoma. Each of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 13 publications
0
29
0
Order By: Relevance
“…These molecules are overexpressed on the surface of malignant melanoma cells compared to the surrounding benign tissue [36]. ICAM-1 is also recognized as a viral attachment receptor for many enteroviruses including CVA13, CVA15 and CVA18 [22]. Phase I/II trials using oncolytic A21 coxsackievirus (Cavatak) have been conducted and found effective and safe [37].…”
Section: It Immunotherapy With Oncolytic Virusesmentioning
confidence: 98%
See 1 more Smart Citation
“…These molecules are overexpressed on the surface of malignant melanoma cells compared to the surrounding benign tissue [36]. ICAM-1 is also recognized as a viral attachment receptor for many enteroviruses including CVA13, CVA15 and CVA18 [22]. Phase I/II trials using oncolytic A21 coxsackievirus (Cavatak) have been conducted and found effective and safe [37].…”
Section: It Immunotherapy With Oncolytic Virusesmentioning
confidence: 98%
“…Viruses can also be genetically modified for selective homing to tumor cells, for example, by genetic alterations in viral capsids or envelops, generating viruses that specifically recognize only tumor-associated surface markers and infect tumor cells [17]. Many DNA and RNA viruses have been used in melanoma treatment, including Newcastle disease virus (NDV) [18], adenovirus [19], herpes simplex virus [20], influenza virus [21], coxsackievirus [22], reovirus [23], vesicular stomatitis virus (VSV) [24], parvovirus [25], vaccinia virus [26,27], measles virus [28] and myxoma virus [29].…”
Section: It Immunotherapy With Oncolytic Virusesmentioning
confidence: 99%
“…Therefore, they lack the genotoxicity caused by integration of the viral genome into the host DNA. In particular, enteroviruses, members of the Picornaviridae family, a diverse group of small RNA viruses have emerged as promising candidates for cancer treatment (6)(7)(8)(9). Their use has several therapeutic advantages: these viruses immediately induce robust cytolytic changes during cell-to-cell infection, they do not possess oncogenes that may lead to tumorigenesis, and they can be easily genetically manipulated by reverse genetics systems for the rescue of positivestrand RNA viruses from complementary DNA (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, sera from patients with stage IV melanoma had undetectable levels of protective neutralizing antibodies for serotypes 13, 15, and 18, while several patients had low levels of antibodies against CVA21, suggesting that a combinatorial approach may be helpful for patients with prior exposure to these viruses. (54)…”
Section: Oncolytic Viruses Used In the Treatment Of Melanomamentioning
confidence: 99%